Einheitlichkeit versus Relecture: Gal 3,6-141 als Testfall - Witulski, Thomas (Liber annuus, 2014)
With the help of these additions the editor reinterpreted the Pauline argumentation, which aimed at the evidence of an Abrahamic sonship (Gal 3:7), towards a conception of a universal δικαιοσύνη of all people - the Jews as well as the Gentiles -, that is realized ἐκ πίστεως and revealed in the reception of the Holy Spirit. This new interpretation can be found for example in Rom 1-3, 4. Thus, he endeavours to integrate the contents of Gal 3:6-13 in the overall theological concept of the apostle, as it is presented - at least in its outline - in Romans. An intention like this can thoroughly be made plausible for an era in which the corpus Paulinum - at least in its first beginnings - was available as a collection of the apostle’s epistles and in which it has been used as a source of a theological teaching authority - a state, which for example 2 Pet 3:15-16 shows.